2021
DOI: 10.21037/tau-20-1047
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen (PSMA)-based imaging in localized and advanced prostate cancer: a narrative review

Abstract: Combined molecular and morphologic imaging modalities have emerged in recent years as an alternative to conventional imaging in prostate cancer (PC). In particular, novel prostate-specific membrane antigen (PSMA) radiotracers have demonstrated increased sensitivity and specificity for the initial staging of men with clinically localized PC, as well as for PC detection in the setting of biochemical recurrence (BCR).Molecular imaging is increasingly used to guide treatment decisions in these patients-though its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Bidakhvidi et al also found positivity rate of 80% using 18F-PSMA-1007 in the detection of lesions in patients with BCR prostate cancer [20]. In addition, the literature from 177Lu-PSMA therapy studies has shown that 20-25% of metastatic castrate resistant prostate cancer (mCRPC) patients are excluded from clinical trials of 177Lu-PSMA therapy due to imaging demonstrating uniformly low PSMA uptake of lesions or discordant lesions showing low PSMA and high 18F-fluorodeoxyglucose (FDG) uptake [22][23][24]. For these patients, other PET imaging agents should be considered such as 18F-fluciclvovine, 18F-FDG, or Sarcophagine-Bombesin imaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Bidakhvidi et al also found positivity rate of 80% using 18F-PSMA-1007 in the detection of lesions in patients with BCR prostate cancer [20]. In addition, the literature from 177Lu-PSMA therapy studies has shown that 20-25% of metastatic castrate resistant prostate cancer (mCRPC) patients are excluded from clinical trials of 177Lu-PSMA therapy due to imaging demonstrating uniformly low PSMA uptake of lesions or discordant lesions showing low PSMA and high 18F-fluorodeoxyglucose (FDG) uptake [22][23][24]. For these patients, other PET imaging agents should be considered such as 18F-fluciclvovine, 18F-FDG, or Sarcophagine-Bombesin imaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, [ 68 Ga]Ga-PSMA-I&T shows greater sensitivity for the detection of primary and metastatic periurethral PCa lesions compared with [ 68 Ga]Ga-PSMA-617, especially for high-grade PCa (GS 8 or above, PSA > 10 ng/mL). However, the kidneys have a much higher uptake of PSMA-I&T than PSMA-617, which is unfavorable for treatment [ 35 36 37 ].…”
Section: Psmamentioning
confidence: 99%
“…1 Conventional imaging modalities used in prostate cancer have traditionally included CT, MRI, and 99m Tclabelled bisphosphonate bone scintigraphy. 2 Although widely available, these modalities have significant limitations, including poor sensitivity and specificity for metastatic disease. 3 A desire to find a better diagnostic imaging technique for prostate cancer led to a focus on prostate-specific membrane antigen (PSMA), which is highly overexpressed in most prostate carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 The most widely studied PSMA radioligand is 68 Ga-labelled PSMA-11 ( 68 Ga-PSMA-11 [ABX Advanced Biochemical Compounds GmbH, Radeberg, Germany]). 2,4 In the Telix-sponsored symposium, 'Improvements in prostate cancer management: focus on imaging and treatment' , delivered on 3 rd July 2022 at the 37 th EAU Annual Congress in Amsterdam, the Netherlands, speakers from three different specialties invited delegates to 'get on board the PSMA train' to optimise the imaging and treatment of prostate cancer, and help improve outcomes for patients.…”
Section: Introductionmentioning
confidence: 99%